The Role of Job Incentive in Rising the Productivity of Workers in The Government Sector A Field Study on Armed Forces Medical Services Staff in Riyadh City 2019 /2020: - Alfaifi, Noura Yahya (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at identify the role of job motivation in raising the productivity of workers in the government sector, by identifying the types of material and moral incentives provided to the medical services employees of the armed forces. For the study, the study sample included (135) of (directors and heads of departments) in the medical services of the armed forces in the city of Riyadh. The results of the study resulted in the following: It was found that the directors and heads of departments in the medical services of the armed forces in the city of Riyadh are neutral with regard to the types of material incentives that most affect the employees of the medical services of the armed forces, with a mean (3.15 out of 5), while they are completely in agreement with regard to the types of incentives. The most influential morale on the medical services employees of the armed forces was with a mean (4.35 out of 5). It was also found that they agreed with the obstacles facing providing appropriate motivation to the medical staff of the armed forces, with a mean (3.68 out of 5). It also turned out that they fully agree with the proposed solutions for the development of motivation systems provided to the medical personnel of the armed forces, with a mean (4.53 out of 5). It was found that there were statistically significant differences in the views of the study sample towards “the most influential material incentives on the medical services employees of the armed forces” due to the administrative level variable, while there are no statistically significant differences between the arithmetic averages of the individuals’ responses around the study axes “the most influential moral incentives on the Staff of the medical services of the armed forces, "obstacles facing the provision of appropriate motivation to the staff of the medical services of the armed forces", "proposed solutions for the development of motivation systems provided to the staff of the medical services of the armed forces" due to the variable of the administrative level, and there are no statistically significant differences between the arithmetic averages of the responses of individuals The study recommended a set of recommendations, the most important of which are: the necessity of having general objectives and a clear vision governing the systems for granting incentives to employees working in the field of medical services, the importance of developing systems and mechanisms for granting Incentives based on performance excellence, not on the basis of seniority or subjective factors. Conducting studies and research on employee motivations and trends when providing Incentives for them, the need for accuracy when preparing periodic reports on the performance of employees and their efforts, to suggest the incentives offered to them.